2014
DOI: 10.3892/ijo.2014.2565
|View full text |Cite
|
Sign up to set email alerts
|

The neurokinin-1 receptor antagonist aprepitant is a promising candidate for the treatment of breast cancer

Abstract: The substance P (SP)/neurokinin (NK)-1 receptor system plays an important role in the development of cancer. No in-depth studies of the involvement of this system in breast cancer (BC) have been carried out, and the action exerted by the drug aprepitant on BC cells is currently unknown. We show the involvement of this system in human BC cell lines: i) these cells express mRNA for the NK-1 receptor; ii) they overexpress NK-1 receptors; iii) the NK-1 receptor is involved in their viability; iv) SP induces their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 53 publications
7
72
0
1
Order By: Relevance
“…This is in line with previous reports by Munoz M. et al describing anti-tumoral activity of fosaprepitant in various adult tumor cell lines [10, 13, 14]. Similar to previous reports, we observed that inhibiting TACR1 with fosaprepitant did not affect all cell lines to the same degree.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is in line with previous reports by Munoz M. et al describing anti-tumoral activity of fosaprepitant in various adult tumor cell lines [10, 13, 14]. Similar to previous reports, we observed that inhibiting TACR1 with fosaprepitant did not affect all cell lines to the same degree.…”
Section: Discussionsupporting
confidence: 94%
“…TACR1 is linked to a variety of physiological and biological processes that include the regulation of neurotransmission, pain, inflammation, cell growth and differentiation [8, 9]. Some recent studies have proposed tachykinin receptor involvement in oncogenesis [1014]. TACR1 activation by substance P initiates phosphoinositide hydrolysis to mobilize intracellular calcium and active calcium-dependent signaling via kinases, such as the SRC kinase [15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, the function of peptides and their receptors in tumors have attracted growing interest, and research efforts show that these peptides and receptors can influence cancer progress. One such target could be SP/NK‐1R system, since it is known that NK‐1R can act as a mitogen on several human cancers . Currently, it is still unknown whether NK‐1R exists the same effect in GBC.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca beyin tümörü in vivo modelinde de, 3 mg/kg/gün dozundaki aprepitantın beyin tümörü çevresindeki ödemi iyileştirdiği açıklanmıştır (31). Meme kanser hücreleri ile yapılan başka bir çalışmada da aprepitantın farklı meme kanser hücreleri olan BT-474, MCF-7 and MDA-MB-468 ve MT-3 üzerinde IC 50 konsantrasyonunun 10-60 μM arasında değiştiği ve kanser hücreleri üzerinde önemli sitotoksik etki yaptığı açıklanmıştır (32).…”
Section: Bulgular Veunclassified